The determinants of website purchases: the role of e-customer loyalty and word-of-mouth - Pereira, H. G.; Cardoso, M.; Dionísio, P. (International Journal of Electronic Marketing and Retailing, 2017)
This paper investigates the influence of several variables on e-loyalty and e-WOM, in the context of personal lifestyle products and services (PLps). Two focus groups are conducted and a questionnaire applied to explore the attitudes and behaviour regarding online shopping in PLps. The results show that overall quality perception, buying experience, website image and personalisation have a positive impact on e-customers’ satisfaction. Also, e-satisfaction has a positive impact on customers’ trust and loyalty, in turn, positively influencing e-WOM. This study also indicates that loyal customers are always looking for new information and available to switch between brands. It is therefore fundamental for organisations to understand and act proactively to ensure a long-term relationship. Two distinct groups of consumers are identified: youngsters and matures, a classification associated to trust. Companies should then apply different strategies to young and mature clients.